The Influence of Problem-Solving Skills and Self-Efficacy on Entrepreneurial Readiness in Culinary Skills Program - Nesya Eka Astari; Suyitno Muslim; Uswatun Hasana (Journal of Pedagogi, 2024)
This study examines the influence of problem-solving skills and self-efficacy on entrepreneurial readiness among participants in a culinary skills program. Given the increasing importance of entrepreneurship in the culinary industry, understanding these factors can enhance educational strategies and support aspiring culinary entrepreneurs. A quantitative research design was employed, utilizing a survey methodology to collect data from 125 culinary skill program participants. The survey measured participants' problem-solving skills, self-efficacy, and entrepreneurial readiness. Data were analyzed using multiple regression analysis to determine the relationships between these variables. The findings reveal that both problem-solving skills and self-efficacy significantly influence entrepreneurial readiness. Specifically, problem-solving skills were found to have a stronger impact, suggesting that participants who are adept at resolving challenges are more prepared for entrepreneurial ventures. Additionally, self-efficacy contributes positively to entrepreneurial readiness, indicating that confidence in one's abilities is crucial in entrepreneurial preparedness. The study concludes that enhancing problem-solving skills and self-efficacy in culinary education programs can significantly boost entrepreneurial readiness.